The Impact of Limited Swimming Experience on Freestyle Swimming Skills in College Students: An Experimental Study Based on Gender with Part and Whole Practice Approaches - Arifin, Z.; Sonjaya, Azhar Ramadhana; Kosasih, Alam Hadi; Nugraha, Luthfi Septiyan (Jurnal Porkes, 2025)
This study investigates the impact of limited swimming experience on students' freestyle swimming skills, with a focus on gender differences. A quasi-experimental design with a pre-test and post-test approach was employed to assess the effectiveness of a swimming training program on 117 male and 10 female students from the Physical Education program at Universitas Garut. The training program, which combined part and whole practice methods, was implemented over an 8-week period. Descriptive statistics, normality tests, and hypothesis testing (Wilcoxon Signed-Ranks Test for male students and paired sample t-test for female students) were used to analyze the data. The results revealed significant improvements in freestyle swimming skills for both male and female groups. For the male group, the mean post-test score increased from 0.00 to 15.70, and for the female group, it increased from 0.00 to 21.20. Statistical analysis confirmed that the improvements were significant for both groups (p < 0.05). When comparing the two groups, the female group showed a greater mean improvement (-21.200) compared to the male group (-15.701), suggesting a more substantial impact of the training on the female participants. Overall, the results of this study indicate that the part practice and whole practice approaches have a significant impact on improving freestyle swimming skills in students with limited swimming experience. Overall, the results of this study indicate that the part practice and whole practice approaches have a significant impact on improving freestyle swimming skills in students with limited swimming experience. This suggests that at the university level, students have a better ability to learn and develop swimming skills more quickly compared to younger age groups. These findings show that although students have limited swimming experience, their adaptive learning abilities allow them to quickly master basic swimming skills, highlighting the potential for effective skill development.